1993
DOI: 10.1038/ng0193-31
|View full text |Cite
|
Sign up to set email alerts
|

A point mutation in the FMR-1 gene associated with fragile X mental retardation

Abstract: The vast majority of patients with fragile X syndrome show a folate-sensitive fragile site at Xq27.3 (FRAXA) at the cytogenetic level, and both amplification of the (CGG)n repeat and hypermethylation of the CpG island in the 5' fragile X gene (FMR-1) at the molecular level. We have studied the FMR-1 gene of a patient with the fragile X phenotype but without cytogenetic expression of FRAXA, a (CGG)n repeat of normal length and an unmethylated CpG island. We find a single point mutation in FMR-1 resulting in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
353
0
3

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 550 publications
(361 citation statements)
references
References 24 publications
5
353
0
3
Order By: Relevance
“…12 One might ask why so few missense mutations have been identified in FMR1? This gene does not appear any less mutable than other typical X-linked genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 One might ask why so few missense mutations have been identified in FMR1? This gene does not appear any less mutable than other typical X-linked genes.…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of conventional mutations have also been demonstrated to lead to FXS. 11,12 Many FMR1 deletions have been reported, with most uncovered through absent or unexpected bands on a Southern blot used to diagnose the full mutation, or by microarray analysis. Nonsense and splice site mutations have also been reported in a limited number of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far the mutations reported at the locus range from deletions of small but critical regions to deletions resulting in removal of the entire gene sequence (16,17,18), small insertions and deletions that lead to loss of function of FMR-1 (19). Point mutation leading to conversion of isoleucine to aspartic acid that results in Iossof function of FMR-1 lead to fragile -X syndrome (20). Molecular Study of FRAXE has shown that the fragility is due to an amplification of a GCC repeat adjacent to a CpG island.…”
Section: Causes Of Fragile X Syndromementioning
confidence: 99%
“…While heterogeneous single base pair substitutions, small deletions, or insertions in the FMR-1 gene could produce a deficiency in the FMR-1 protein (FMRP) [Wöhrle et al, 1992;De Boulle et al, 1993;de Vries et al, 1993;Ashley et al, 1993], aberrations in other X-linked mental retardation genes, not identified to date, could also play a role in the causation of mental retardation in cytogenetically normal males.…”
mentioning
confidence: 99%